Family Presence and Visitation Practices in Latin American PICUs: An International Survey - González-Dambrauskas, Sebastián; Mislej, Cecilia; Vásquez-Hoyos, Pablo; Rotta, Alexandre Tellechea (Journal of Pediatric Intensive Care, 2020)
Over the last two decades, there has been a worldwide cultural shift toward family-centered intensive care. In this article, we conducted a survey of 47 pediatric intensive care units (PICUs) across 11 Latin American countries to assess visitation practices and bedside family presence (with a 97.9% response rate). All PICUs had at least some form of parental visitation. The prevalence of unrestricted (24 hours/day) parental visitation was 63%. Sibling visitation was permitted in 23% of PICUs, while 35% allowed family presence during procedures, and 46% during resuscitation. Only 1 PICU allowed pet visitation. Family visitation and bedside presence are still restrictive in Latin American PICUs, with wide practice variation among the various intensive care units.
Keywords: family; visiting policy; pediatric intensive care